Pengaruh iradiasi sinar gamma [60Co] terhadap kutudaun Macrosiphoniella sanborni (Gillette) (Hemiptera: Aphididae) dan kualitas bunga potong krisan (Chrysanthemum morifolium var. Jimba Lima) - Sri Endang Purwanti; Idham Sakti Harahap; Dadang Dadang; Murni Indarwatmi (Jurnal Entomologi Indonesia, 2022)
Chrysanthemum cut flower is a popular flower that has economic values. Infestation of Macrosiphoniella sanborni (Gillette) on chrysanthemum cut flowers can reduce the aesthetics of the flower, cause economic loss, and impose restriction in the internasional trading. The aim of this research was to determine the effective dose of [60Co] gamma irradiation in controlling M. sanborni on chrysanthemum cut flower and to evaluate the effect on quality of chrysanthemum cut flower (Chrysanthemum morifolium cv. Jimba Lima). The research was conducted in several steps: collection and mass rearing of M. sanborni, relative toxicity test of [60Co] gamma irradiation against M. sanborni, sublethal dose test on adults, and evaluation of the effect on the quality of cut flower. The dosages used in relative toxicity and sublethal experiment were 50–200 Gy and 200–250 Gy. The results showed that the LD99 value of adult was 1,092.982 Gy. A sublethal dose test was performed because C. morifolium cv. Jimba Lima has radiotolerance with dose below 300 Gy. The effective dose of [60Co] gamma irradiation against M. sanborni was 200 Gy. Application of this dose on first instar nymph showed the survival development reached only until the third instar nymph and it reached the adult stage when applied on second, third, and fourth instar nymphs. Application on the adult stage showed that the aphids can still reproduce first progenies but only in a small number (5.35%). Application of 200 Gy did not have negative effect on the quality of chrysanthemum cut flower within 9 days.